ACCOUNT JUAH'S CONTRIBUTION FOR THE COMMUNITY OF WEST KALIMANTAN: Kontribusi Tampun Juah Untuk Masyarakat Kalimantan Barat - Nunik Esti Utami (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
This study aims to This research aims to: (1) Dayak tribe in West Kalimantan and the origin of Tampun Juah; (2) Tampun Juah for the people of West Kalimantan. The research method used in this study is a historical method written in a descriptive-analytic manner with cultural and social integration. The series of research is described in several stages, namely heuristics. Second, verification. Third, interpretation. Fourth, historiography. The results of this study note that: (1) The diversity of the Dayak tribe. (2) Tampun Juah is a place of origin for the identity of the Dayak tribe, language, culture, and the creation of Malian customary law, namely customary law, customs for the benefit of the people of West Kalimantan..